A 32-Year Analysis of Occupational Safety and Health in Ecuador: Regulatory Impact on Workplace Morbidity and Mortality - Gómez-García, Antonio Ramón; Vega Chica , Mayra Liuviana; Yturralde, Mg. Juan Gabriel (Journal of Ecohumanism, 2025)
Background: This study analyzed the evolution of work-related injuries and fatalities in the Republic of Ecuador from 1990 to 2022 using a time-series trend analysis, with the secondary objective of assessing the impact of public policies. Methods: The data were obtained from the administrative records of the Ecuadorian Social Security Institute and categorized into six periods based on the introduction of legal frameworks regulating social security. Epidemiological indicators, including morbidity, mortality, and lethality rates, were calculated using the working population insured and protected by General Insurance for Occupational Risk. Results: The results showed that between 1990 and 2022, 269,969 work-related injuries were classified, of which 2% were fatal (5,352 deaths). The overall morbidity rate remained stable, whereas the overall mortality and case fatality rates exhibited significant declining trends. Conclusion: Trend variations and significant differences between periods were observed for each indicator. Despite efforts to improve OSH in Ecuador, the lack of a consistent downward trend highlights the regulatory framework’s limited effectiveness. The findings suggest the need for a more in-depth analysis to explain the factors underlying the differential effects between periods and the establishment of a robust national OSH policy aligned with ILO Conventions No. 155 and No. 187 to promote a proactive safety culture.